The analgesics used in the abortive treatment of migraine: When did they arrive in Brazil? - Pereira, Mariana Leite; Moreira, Fernando Jacó Silva; Coelho, Rayssa Fernandes Souza; Oliveira, Lucas Aguiar Alencar; Ribeiro, Allyson Coelho; Martins, Augusto César Beserra; Dantas, José Hugo Andrade Santos; Gayoso-Almendra, Isadora Almendra Costa Coelho; Brandão, Ítalo Araújo Rios; Gomes, July Lima; Souza, Kamilla Gomes Sales; Leal, Laysa Moura Cardoso; et al. (Headache Medicine, 2017)
Analgesics are medications that slow or stop nerve pathways, suppressing pain. In this group of drugs are dipyrone, paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs) and narcotics. Until the end of the 19th century, there was no analgesic and / or anti-inflammatory drug in Brazil for the abortive treatment of migraine. Acetylsalicylic acid was the first to arrive in Brazil in 1922; and dipyrone, the second, in 1922. Subsequently, dihydroergotamine, paracetamol, the other NSAIDs and, finally, a specific drug, the triptans, were synthesized. Despite this therapeutic arsenal, a greater effort is still required for the development of new drugs and improvement of existing drugs.